The Effect of Character Building on Student Discipline at Karitas Catholic High School in Tomohon - Bernadina Waha Labuan; Maikel Billy Ausa; Virginia Scolastica Ndonga; Margareta Aminiarti; Nikolaus Fasak (International Journal Labs, 2026)
This study investigates the influence of character development on student discipline at Karitas Catholic High School, Tomohon. In the context of education, fostering student discipline is essential for creating an orderly and conducive learning environment, as well as developing responsible and socially aware individuals. Despite the recognized importance of character education, gaps remain in systematically implementing programs that translate moral values into measurable behavioral outcomes. The purpose of this study is to examine how structured character development programs affect various aspects of student discipline, including punctuality, adherence to school rules, task completion, and ethical conduct. The research employed a quantitative correlational design with a sample of 179 students from grades 10 and 11, selected through purposive sampling. Data were collected using a 50-item Likert-scale questionnaire measuring character development and discipline, validated through expert review and pilot testing, with reliability confirmed via Cronbach's alpha. Data were analyzed using SPSS software and Pearson Product-Moment correlation to determine the strength and significance of the relationship between the variables. The findings indicate a very strong and significant positive correlation (r = 0.850, p < 0.05), demonstrating that higher levels of character development are associated with increased student discipline. The results highlight the critical role of planned and continuous character education in shaping student behavior, underscoring its importance as a foundation for academic success and moral development.